2018
DOI: 10.1111/cea.13078
|View full text |Cite
|
Sign up to set email alerts
|

Predicting reactivity threshold in children with anaphylaxis to peanut

Abstract: In children with anaphylaxis to peanut, basophil activation, peanut SPT and the ratio of peanut s-IgE/total IgE were associated with reactivity threshold and LOAEL, but not with allergy reaction severity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(46 citation statements)
references
References 86 publications
(123 reference statements)
0
46
0
Order By: Relevance
“…The DBPCFC was defined positive with at least two moderate objective symptoms in one or more organ systems according to Bock's criteria . Cumulated peanut protein (mg) intake at positive DBPCFC was recorded as the reactivity threshold, whereas the lowest observed adverse effect level (LOAEL) was calculated post hoc and defined as the amount of peanut protein ingested eliciting mild, objective symptoms . Enrolment in the TAKE‐AWAY trial required a positive DBPCFC with a reactivity threshold > 3 mg peanut protein .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The DBPCFC was defined positive with at least two moderate objective symptoms in one or more organ systems according to Bock's criteria . Cumulated peanut protein (mg) intake at positive DBPCFC was recorded as the reactivity threshold, whereas the lowest observed adverse effect level (LOAEL) was calculated post hoc and defined as the amount of peanut protein ingested eliciting mild, objective symptoms . Enrolment in the TAKE‐AWAY trial required a positive DBPCFC with a reactivity threshold > 3 mg peanut protein .…”
Section: Methodsmentioning
confidence: 99%
“…The feasibility of OIT is likely to be influenced by AEs, while other factors are less well known. A low starting dose with a high maintenance dose increases the number of dose steps in an already time‐consuming long‐term protocol, thereby excluding patients with less time resources …”
Section: Introductionmentioning
confidence: 99%
“…Basophil allergen threshold sensitivity was independently associated with clinical threshold and BAT predicted reaction severity. These findings were corroborated by Reier‐Nilsen et al who found that BAT correlated significantly with LOAEL . Although not readily available in clinical practice, BAT may have a place in the future to predict food allergy thresholds and help guide clinical decisions.…”
Section: Future Perspectivesmentioning
confidence: 53%
“…Furthermore, sIgE and SPT size did not correlate with objective reactions after the single‐dose peanut challenge in the PATS study . However, a recent randomized controlled trial by Reier‐Nilson et al demonstrated that SPT size and peanut sIgE/total IgE ratio were significantly associated with reaction threshold. Similarly, Blumchen et al measured biological markers during food challenge and found that MED was inversely correlated with peanut and Ara h 2‐specific IgE, SPTs, basophil activation and Th2 cytokines produced by peripheral blood mononuclear cells .…”
Section: Factors Affecting Food Allergen Thresholdmentioning
confidence: 84%
“…Children 5-15 years old with sensitization to peanut by a peanut skin prick test (SPT) ≥3 mm and/or a specific IgE (s-IgE) to peanut ≥0.35 kUA/L or with a history of systemic reactions to peanut were screened for study enrollment at the Department of Pediatric and Adolescent Medicine, Oslo University Hospital, Ullevål, Norway, from February 2014 to June 2015, as previously described. 18 Enrollment required a positive double-blind placebo-controlled food challenge (DBPCFC) defined by objective symptoms in ≥2 organ systems and a reactivity threshold >3 mg peanut protein 18 . Anaphylaxis was defined according to the European Academy of Allergy and Clinical Immunology criteria.…”
Section: Methodsmentioning
confidence: 99%